Neil Flambé and the Crusaders curse - Sylvester, Kevin (Simon & Schuster Books for Young Readers, 2012)
The sudden disappearance of fifteen-year-old Neil Flambé's skills as a world-class chef leads to the closing of his restaurant, a cook-off to save his reputation, and the discovery of a dark curse that has plagued Flambé cooks for centuries.